INTERPRETATION OF LEXICAL CONCEPTS IN MOTHER LANGUAGE-READING LITERACY LESSONS - Xujanov Xolbuta Xudoyqulovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article provides information on the formation of an idea of ​​​​lexical concepts in primary school native language classes. The article aims to identify effective forms and methods of organizing the formation of an idea of ​​​​the system of lexical concepts in primary school native language and reading lessons based on methods and technologies.